Is the DBU–CO2 adduct stable in ionic liquid media? - Giovanni Rodrigues Morselli; Philippi, Frederik; Pedro Henrique de Paula Sabanay; Reinaldo Camino Bazito; Margarida Costa Gomes; Ando, Rômulo Augusto (Physical chemistry chemical physics : PCCP, 2025)
The DBU–CO2 adduct was characterized for the first time by 13C NMR with labelled 13CO2 and IR spectroscopy. Theoretical calculations were crucial to determine that the adduct is stable in ionic liquid medium in the presence of water. These findings provide new insights into superbase–CO2 interactions, unveiling a new potential route to CO2 activation.